2022
DOI: 10.1158/2159-8290.cd-22-0192
|View full text |Cite
|
Sign up to set email alerts
|

Stromal Reprogramming by FAK Inhibition Overcomes Radiation Resistance to Allow for Immune Priming and Response to Checkpoint Blockade

Abstract: The effects of radiation therapy (RT) on tumor immunity in PDAC are not well understood. To better understand if RT can prime antigen-specific T cell responses, we analyzed human PDAC tissues and mouse models. In both settings, there was little evidence of RT-induced T cell priming. Using in-vitro systems, we found that tumor stromal components, including fibroblasts and collagen, cooperate to blunt RT efficacy and impair RT-induced interferon signaling. Focal Adhesion Kinase (FAK) inhibition rescued RT effica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 93 publications
0
33
0
Order By: Relevance
“…We and others have previously shown that a collagen-dense extracellular matrix promotes cancer disease progression and impairs treatment response 21 , 22 , 30 . Given that myMAFs are the predominant source of collagen-rich ECM and that macrophage depletion markedly reduced their abundance, we next aimed to elucidate how macrophages regulate myMAF activation and function.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…We and others have previously shown that a collagen-dense extracellular matrix promotes cancer disease progression and impairs treatment response 21 , 22 , 30 . Given that myMAFs are the predominant source of collagen-rich ECM and that macrophage depletion markedly reduced their abundance, we next aimed to elucidate how macrophages regulate myMAF activation and function.…”
Section: Resultsmentioning
confidence: 96%
“…Although we see increased levels of active CD8+ T cells in both HStC-STAT3 cKO and STAT3i tumours, the majority of CD8+ T cells remain dysfunctional. Recent efforts combining ICT with stromal reprogramming has shown promising results in preclinical mouse models of PDAC 30 , 57 . However, the JAK/STAT pathway also plays a central role in type 1 interferon-driven induction of T cell cytotoxicity 58 , rendering STAT3i largely incompatible in combination with ICT.…”
Section: Discussionmentioning
confidence: 99%
“…The pancreatic TME presents multiple immune suppressive hurdles that must be overcome for effective immunotherapy, including (a) a desmoplastic stroma contributing to physical exclusion and chemical inhibition of immune cells, (b) a poorly vascularized matrix leading to poor delivery of drugs and infiltration of peripheral immune cells, (c) a lack of cytotoxic NK and T lymphocytes that drive tumor eradication, (d) suppressive myeloid populations that inhibit lymphocyte activation, (e) few DCs to present antigen to T cells, and (f) low neo-antigen loads and dysfunctional antigen presentation circuitry in tumor cells allowing them to escape immune detection ( 2, 5 ). Though other groups have started to show promising early clinical results with neo-antigen vaccines ( 37 ), myeloid reprogramming ( 38, 39 ), and stromal remodeling agents ( 40, 41 ) that target some of these immune suppressive mechanisms, none of these therapies have yet to be clinically approved. Here we designed a novel multi-pronged approach combining localized innate immune agonist and systemic tumor-targeting senescence-inducing therapies to target many of the immune suppressive mechanisms in PDAC simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, other studies show that neoadjuvant chemotherapy shifts the immune microenvironment toward an antitumor state, associated with improved survival 8 . Nevertheless, there are many trials examining the efficacy of other drugs, ranging from paricalcitol (a vitamin D analog believed to reduce growth of malignant cells) to inhibitors of specific intracellular pathways, including hepatocyte growth factor), poly adenosine diphosphate‐ribose polymerase (PARP), focal adhesion kinase (FAK) and other tyrosine kinases 9–11 . Vaccination represents another innovative strategy: GVAX, composed of granulocyte‐macrophage colony‐stimulating factor‐secreting allogeneic pancreatic tumor cells, induces T cells against a broad array of PDAC antigens and is being employed in both resectable and advanced disease, in combination with chemo‐ or immunotherapy.…”
Section: Clinical Advancesmentioning
confidence: 99%